ANALISIS TERHADAP STATUS HUKUM ANAK AKIBAT LOKIKA SANGGRAHA MENURUT HUKUM ADAT BALI - ranciscadellaandriani; Nurhayati Mardin; Susi Susilawati (Universitas Tadulako, 2025)
Indonesia, as a country rich in cultural and customary diversity, faces challenges in regulating marriage practices and Lokika Sanggraha, particularly regarding the unclear legal status of children born outside of legal wedlock. The inconsistency between customary law and positive law complicates the recognition of children's status and the implementation of sacred and magical customary marriages. The practice of Lokika Sanggraha, or cohabitation, which contradicts religious and moral norms, gives rise to various social and administrative problems, such as difficulties in obtaining identity documents, legal recognition, and inheritance rights for children. National provisions, such as the Marriage Law and the Population Administration Law, do not explicitly regulate the status and legal protection of children from extramarital relationships, thus triggering legal uncertainty and potential discrimination. This study aims to determine Balinese customary law in addressing the status of children resulting from Lokika Sanggraha. Using an empirical juridical approach in Parigi Moutong, it shows that conservative Balinese customs reinforce stigma and limit access for children, resulting from Lokika Sanggraha's customary rights and inheritance. Although the Child Protection Law guarantees the right to identity, education, and protection from discrimination, the absence of clear regulations regarding children resulting from Lokika Sanggraha results in weak legal certainty and regulatory enforcement. Therefore, legal consolidation that refers to the best interests of children between customary law and national law is needed through dialogue, education, and inclusive and progressive legal reform so that children's rights remain fairly protected.